How have recent temperature changes affected the efficiency of ocean biological carbon export?. Issue 4 (22nd June 2017) - Cael, B. B.; Bisson, Kelsey; Follows, Michael J.
Abstract: The ocean's large, microbially mediated reservoirs of carbon are intimately connected with atmospheric CO2 and climate, yet quantifying the feedbacks between them remains an unresolved challenge. Through an idealized mechanistic model, we consider the impact of documented climate change during the past few decades on the efficiency of biological carbon export out of the surface ocean. This model is grounded in universal metabolic phenomena, describing export efficiency's temperature dependence in terms of the differential temperature sensitivity of phototrophic and heterotrophic metabolism. Temperature changes are suggested to have caused a statistically significant decrease in export efficiency of 1.5% ± 0.4% over the past 33 yr. Larger changes are suggested in the midlatitudes and Arctic. This interpretation is robust across multiple sea surface temperature and net primary production data products. The same metabolic mechanism may have resulted in much larger changes e.g., in response to the large temperature shifts between glacial and interglacial time periods.